The racial and ethnic gap in behavioral measures rivals the gender gap in the United States - Aurélie Dariel; John C. Ham; Nikos Nikiforakis; Jan Stoop (Proceedings of the National Academy of Sciences, 2026)
Behavioral research has been criticized for relying on demographically narrow WEIRD samples-Western, Educated, Industrialized, Rich, and Democratic. While recent work has expanded to explore cross-country behavioral differences, the study of within-country variation has largely focused on gender, ignoring race and ethnicity—so much so that the “W” in WEIRD might as well stand for “White.” Using incentivized tasks and a large, stratified sample of U.S. adults, we document substantial racial and ethnic gaps in competitiveness and risk tolerance both of which are widely studied behavioral measures: (non-Hispanic) Whites are less competitive and more risk tolerant than Blacks and Hispanics. These gaps are comparable in magnitude to the corresponding gender gaps in our sample. Notably, gender differences do not generalize across racial and ethnic groups: Whereas Whites and Hispanics exhibit gender gaps in competitiveness and risk tolerance, Black women neither shy away from competition nor are they less risk tolerant than Black men. These findings challenge prevailing generalizations in the literature and underscore the importance of examining race and ethnicity in behavioral research.